Redox Regulation of LAT Enhances T Cell-Mediated Inflammation - Jaime James; Ana Coelho; Gonzalo Fernandez Lahore; Clara M. Hernandez; Florian Forster; Bernard Malissen; Rikard Holmdahl (MDPI AG, 2024)
The positional cloning of single nucleotide polymorphisms (SNPs) of the neutrophil cytosolic factor 1 (Ncf1) gene, advocating that a low oxidative burst drives autoimmune disease, demands an understanding of the underlying molecular causes. A cellular target could be T cells, which have been shown to be regulated by reactive oxygen species (ROS). However, the pathways by which ROS mediate T cell signaling remain unclear. The adaptor molecule linker for activation of T cells (LAT) is essential for coupling T cell receptor-mediated antigen recognition to downstream responses, and it contains several cysteine residues that have previously been suggested to be involved in redox regulation. To address the possibility that ROS regulate T cell-dependent inflammation through LAT, we established a mouse strain with cysteine-to-serine mutations at positions 120 and 172 (LATSS). We found that redox regulation of LAT through C120 and C172 mediate its localization and phosphorylation. LATSS mice had reduced numbers of double-positive thymocytes and naïve peripheral T cells. Importantly, redox insensitivity of LAT enhanced T cell-dependent autoimmune inflammation in collagen-induced arthritis (CIA), a mouse model of rheumatoid arthritis (RA). This effect was reversed on an NCF1-mutated (NCF1m1j), ROS-deficient, background. Overall, our data show that LAT is redox-regulated, acts to repress T cell activation, and is targeted by ROS induced by NCF1 in antigen-presenting cells (APCs).